2021
DOI: 10.1101/2021.07.08.451588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structure of alpha-synuclein fibrils amplified by PMCA from PD and MSA patient brains

Abstract: Synucleinopathies are neurodegenerative diseases related to the aggregation of the protein alpha-synuclein (aSyn). Among these diseases, Parkinson’s disease (PD) and multiple system atrophy (MSA) are most prevalent. aSyn can readily form different fibrillar polymorphs, if exposed to an air-water interface or by templating with pre-existing fibrils. We here report the structures of three fibrillar polymorphs that were obtained after seeding monomeric aSyn with PD and MSA patients brain homogenates using protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 85 publications
6
32
0
Order By: Relevance
“…Meanwhile, we notice two structural studies of α-syn fibrils amplified from PD brain homogenates post on BioRxiv recently. 13,28 Interestingly, in one study, the reported α-syn fibril structures are very similar to our Type 1a and 1b fibrils. 28 While, in the other study that applied four short cycles rather than one long cycle of amplification, the reported fibril structures are distinctive from any known wild-type α-syn fibril structures but similar to that formed by Y39-phosphorylated α-syn 13,29 , which may reflect the existence of pY39-like fibril conformation in the PD brain.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Meanwhile, we notice two structural studies of α-syn fibrils amplified from PD brain homogenates post on BioRxiv recently. 13,28 Interestingly, in one study, the reported α-syn fibril structures are very similar to our Type 1a and 1b fibrils. 28 While, in the other study that applied four short cycles rather than one long cycle of amplification, the reported fibril structures are distinctive from any known wild-type α-syn fibril structures but similar to that formed by Y39-phosphorylated α-syn 13,29 , which may reflect the existence of pY39-like fibril conformation in the PD brain.…”
Section: Discussionsupporting
confidence: 85%
“…13,28 Interestingly, in one study, the reported α-syn fibril structures are very similar to our Type 1a and 1b fibrils. 28 While, in the other study that applied four short cycles rather than one long cycle of amplification, the reported fibril structures are distinctive from any known wild-type α-syn fibril structures but similar to that formed by Y39-phosphorylated α-syn 13,29 , which may reflect the existence of pY39-like fibril conformation in the PD brain. Taken together, the amplified fibrils from patients biological fluid and tissue samples may partially represent their mother fibrils.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, structural verification of seeds and seeded aggregates is required. For α-synuclein and immunoglobulin lightchain, cryo-EM has shown that using similar amplification methods, the structures of seeded filaments differed from those of the seeds under the conditions used (Burger et al, 2021;Lövestam et al, 2021;Radamaker et al, 2021). Full-length human tau is highly soluble, but truncated proteins encompassing the repeat region readily assemble into filaments that resemble AD PHFs by negative staining.…”
Section: Introductionmentioning
confidence: 99%
“…However, they may not always amplify the predominant filamentous assemblies Therefore, structural verification of seeds and seeded aggregates is required. For α-synuclein and immunoglobulin light-chain, cryo-EM has shown that using similar amplification methods, the structures of seeded filaments were not the same as those of the seeds (Burger et al, 2021;Lövestam et al, 2021;Radamaker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%